Toxicity of Clove Oil Nanoparticle Againts (Aphis gossypii) on Chili (Capsicum annum) and Its Predator (Cheilomenes sexmaculata): Toxicity of CO-NPs againts A. gossypii and C. sexmaculata - Ikawati, Silvi; Boangmanalu, Maslina; Choliq, Fery Abdul; Aji Pamungkas, Bayu (Journal of Tropical Life Science, 2024)
One of the pests that cause economic losses in Chili (Capsicum annum L.) is aphid (Aphis gossypii Glover) (Hemiptera: Aphididae). Therefore, it is necessary to carry out alternative controls that are not damaging and detrimental to the surrounding environment including against beneficial organisms such as the natural enemy Cheilomenes sexmaculata Fabricius (Coleoptera: Coccinellidae). Clove oil and the formulation of essential oils in the form of nanoparticles have been used as a botanical pesticide. The purpose of this work is to determine the toxicity of a clove oil nanoformulation against aphids (A. gossypii) and the six-spotted zigzag ladybird predator C. sexmaculata. This work has six treatments and four replications using a fully randomized design. The results showed that clove oil nanoparticles (CO-NPs) significantly affected mortality and decreased the number of offspring of A. gossypii. The average size of the tested nanoparticles was 166.38 nm and the average zeta potential value of the tested nanoparticles was -19 mV. The CO-NPs can affect the increase in mortality and decrease in the offspring number of A. gossypii. The LC50 value of A. gossypii was 0.32% at the time of observation 48 hours after application while the LT50 value was 3 hours at a concentration of 1.2%. The percentage of decrease in the number of offspring reached 95.01% at a concentration of 1.2%. Results of calculating the selectivity ratio value (SR) showed that CO-NPs are selective against predators C. sexmaculata, with the SR value <1.